2007
DOI: 10.1016/j.ejrad.2007.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpolarized 129Xe MRI: A viable functional lung imaging modality?

Abstract: The majority of researchers investigating hyperpolarized gas MRI as a candidate functional lung imaging modality have used 3 He as their imaging agent of choice rather than 129 Xe. This preference has been predominantly due to, 3 He providing stronger signals due to higher levels of polarization and higher gyromagnetic ratio, as well as its being easily available to more researchers due to availability of polarizers (USA) or ease of gas transport (Europe). Most researchers agree, however, that hyperpolarized 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
133
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(134 citation statements)
references
References 22 publications
(48 reference statements)
1
133
0
Order By: Relevance
“…It has been reported that several physiological quantities related to these processes were globally evaluated from measurements of alveolar gas uptake dynamics using CSSR in animals 30,[42][43][44][45] and humans. 39,46,47 Whole-lung spectroscopy, however, limits the assessments to be accepted as global measures without any information about the spatial distribution in the lung. An extension of spectroscopybased methods to imaging-based methods is an important step toward identifying a region with impaired function with higher sensitivity and evaluation of its variation in the whole lung.…”
Section: Dissolved-phase 129 Xe Mrimentioning
confidence: 99%
“…It has been reported that several physiological quantities related to these processes were globally evaluated from measurements of alveolar gas uptake dynamics using CSSR in animals 30,[42][43][44][45] and humans. 39,46,47 Whole-lung spectroscopy, however, limits the assessments to be accepted as global measures without any information about the spatial distribution in the lung. An extension of spectroscopybased methods to imaging-based methods is an important step toward identifying a region with impaired function with higher sensitivity and evaluation of its variation in the whole lung.…”
Section: Dissolved-phase 129 Xe Mrimentioning
confidence: 99%
“…(156) However, improvement in hyperpolarization systems has meant that 129-Xenon MR imaging is making rapid strides forward, giving new insight in lung function. (160)(161)(162).One of the main features of hyperpolarized gas imaging is that the signal introduced in the system is so high that imaging is less dependent on field strength than is the case for proton imaging, and this has advantages as lower field-strength magnets may result in fewer artifacts. (163)(164)(165) A main disadvantage to this technique is that the contrast is exogenous, and is non-renewable.…”
Section: Hyperpolarized Gas Imagingmentioning
confidence: 99%
“…Measurement of p A O 2 has previously been reported using spin-lattice relaxation rates, R 1 , of both hyperpolarized 3 He (13)(14)(15)(16)(17) and 129 Xe (5). Although most previous studies have employed 3 He due to its higher signal-to-noise ratio (SNR), 3 He has a very low natural abundance, making it a poor candidate for widespread clinical use.…”
Section: Introductionmentioning
confidence: 99%